2022
DOI: 10.1097/inf.0000000000003564
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Children: Correlation Between Epidemiologic, Clinical Characteristics, and RT-qPCR Cycle Threshold Values

Abstract: Background: Initially, the impact of SARS-CoV-2 infection on children was unknown. Standard COVID-19 diagnosis is confirmed using real-time qPCR. Cycle threshold (Ct) values of RT-qPCR are inversely proportional to viral load and the test indirectly quantifies viral RNA copy numbers. The objective of this study was to determine the correlation between epidemiology, clinical characteristics, severity of confirmed COVID-19 cases, and Ct values. Methods: An observational, analytical, cross-sectional study. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…These results concur with findings from global studies conducted during the first year of the pandemic, in which infection rates were lowest among infants and young children in communities ( 32 , 45 ) and households ( 46 48 ), with household secondary attack rates ranging from 5% to 55% and exhibiting marked variation across age groups ( 34 , 49 52 ). In an observational study of SARS-CoV-2 infected children, infants < 2 years of age were observed to have lower viral loads but lower prevalence of symptomatic cases as compared to children 2 years and older ( 53 ). We observed a slightly higher prevalence of PCR positivity and symptomatic cases among infants as compared to other household children aged 2-5 years in our study, though differences in PCR positivity may reflect age-related differences in exposures related to care and feeding, testing, and parental perception of symptoms and risks that influenced testing.…”
Section: Discussionmentioning
confidence: 99%
“…These results concur with findings from global studies conducted during the first year of the pandemic, in which infection rates were lowest among infants and young children in communities ( 32 , 45 ) and households ( 46 48 ), with household secondary attack rates ranging from 5% to 55% and exhibiting marked variation across age groups ( 34 , 49 52 ). In an observational study of SARS-CoV-2 infected children, infants < 2 years of age were observed to have lower viral loads but lower prevalence of symptomatic cases as compared to children 2 years and older ( 53 ). We observed a slightly higher prevalence of PCR positivity and symptomatic cases among infants as compared to other household children aged 2-5 years in our study, though differences in PCR positivity may reflect age-related differences in exposures related to care and feeding, testing, and parental perception of symptoms and risks that influenced testing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Gentile et al. report lower CT values in children <2 compared to those age 2–17 [22] . Jiménez et al.…”
Section: Discussionmentioning
confidence: 98%
“…The need for a high viral load seems not to pose a problem, as most of the Ct values in symptomatic SARS-CoV-2-positive patients are lower than 20, especially when the clinical samples are collected within 10 days since symptom onset [ 23 , 24 ]. Moreover, the high viral load does not prevent performance of the test, as greater risk of transmission, as in an outbreak scenario, is associated with increased viral load values and positive relationships between viral load and infectiousness [ 25 ].…”
Section: Discussionmentioning
confidence: 99%